Introducing an additional concept in chemical bonding: How effectively can chemistry students comprehend charge-shift bonding? - Filip Stašević; Slađana Đorđević; Slavko Radenković; Jelena Đurđević Nikolić (Macedonian Journal of Chemistry and Chemical Engineering)
The development of more modern and effective strategies for teaching chemical bonding theory is a key objective within the chemistry education community. A solid understanding of this concept is essential for comprehending a range of chemistry topics, including the physical and chemical properties of substances, chemical thermodynamics, and polymers – all of which play a vital role in real-world applications. Integrating valence bond (VB) theory, with its strong interpretative capabilities, into the teaching of chemical bonding through information and communication technologies (ICT) can help simplify complex ideas and enhance students' comprehension. This paper presents a structured approach to explaining charge-shift bonding (CSB) within the VB theory framework by calculating the contributions of covalent and ionic VB structures, bond dissociation energy, and resonance energy. Additionally, it introduces unique teaching materials for university teachers and students, combining contemporary teaching tools with classical VB theory. The study involved 47 chemistry students, and the effectiveness of the practical training was assessed using three questionnaires, two knowledge tests (pre-test and post-test), and one survey. Results showed that MSc and PhD students were able to successfully grasp the fundamental concepts of CSB using the proposed approach, while undergraduate students encountered more difficulty. The practical class can serve as a valuable supplement to traditional upper-level instruction on chemical bonding, helping educators and students stay informed about more accurate and modern explanations of bonding in certain molecules.